Ion beam synthesis of silicon carbide - Intarasiri S. (2014)
Formation and crystallization of a thin near-surface layer of silicon carbide on a silicon substrate, created by ion-beam synthesis (IBS), are discussed. 80 and 40 keV carbon ions were implanted into a (1 0 0) high-purity p-type silicon substrate at room temperature and 400°C, respectively, using doses in excess of 1017 ions/cm2. Elastic recoil detection analysis (ERDA) technique, developed for routine atomic depth profiling at the Angstrom laboratory, Uppsala University, Sweden, was used to investigate the depth distributions of implanted-ions. Infrared transmittance measurement was used as an indication of SiC in the implanted Si substrate. For the samples implanted at high temperature, the results show the existence of a peak at 797 cm-1, indicating the presence of β-SiC, already directly formed during the implantation without post-implantation annealing. While for the samples implanted at room temperature, starting with the band of amorphous Si-C network, the crystalline SiC appears at the annealing temperature as low as 900°C. In both cases, during further annealing in vacuum, the peak grows in height and narrows in width (according to the measured FWHM) with increasing annealing temperature, indicating a further growth of the SiC layer. However, for thermal annealing at 1000°C in a vacuum furnace the SiC crystallization was not completed and crystal imperfection where still present. Complementary to IR, Raman scattering measurements were performed. Although no direct evidence of SiC vibrations were observed, the appearance and disappearance of both Si-Si and C-C related bands points out to the formation of silicon and carbon clusters in the implanted layer. © 2005 Trans Tech Publications, Switzerland.